A Study of Micronucleus Induction with Methyl Formate and 2-Methylbutane in Bone Marrow Cells of Male ICR Mice - Soo-Jin Kim; Kyung-Taek Rim; Min-Gu Kang; Jong-Kyu Kim; Yong-Hyun Chung; Jeong-Sun Yang (Safety and Health at Work, 2010)
Objectives: We investigated the genotoxicity of two chemicals, methyl formate and 2-methylbutane, using male ICR mice bone marrow cells for the screening of micronucleus induction. Although these two chemicals have already been tested numerous times, a micronucleus test has not been conducted and the amounts used have recently been increased. Methods: 7 week male ICR mice were tested at dosages of 250, 500, and 1,000 mg/kg for methyl formate and 500, 1,000, and 2,000 mg/kg for 2-methlybutane, respectively. After 24 hours of oral administration with the two chemicals, the mice were sacrificed and their bone marrow cells were prepared for smearing slides. Results: As a result of counting the micronucleated polychromatic erythrocyte (MNPCE) of 2,000 polychromatic erythrocytes (PCE), all treated groups expressed no statistically significant increase of MNPCE compared to the negative control group. There were no clinical signs related with the oral exposure of these two chemicals. Conclusion: It was concluded that the two chemicals did not induce micronucleus in the bone marrow cells of ICR mice, and there was no direct proportion with dosage. These results indicate that the two chemicals have no mutagenic potential under each study condition.